Methodological Critique of Concussive and Non-Concussive Dual Task Walking Assessments: A Scoping Review - Mitchell, Courtney Jade; Cronin, John (MDPI AG, 2023)
OBJECTIVE: To understand the methodological approaches taken by various research groups and determine the kinematic variables that could consistently and reliably differentiate between concussed and non-concussed individuals. METHODS: MEDLINE via PubMed, CINAHL Complete via EBSCO, EBSCOhost, SPORTDiscus, and Scopus were searched from inception until 31 December 2021, using key terms related to concussion, mild traumatic brain injury, gait, cognition and dual task. Studies that reported spatiotemporal kinematic outcomes were included. Data were extracted using a customised spreadsheet, including detailed information on participant characteristics, assessment protocols, equipment used, and outcomes. RESULTS: Twenty-three studies involving 1030 participants met the inclusion criteria. Ten outcome measures were reported across these articles. Some metrics such as gait velocity and stride length may be promising but are limited by the status of the current research; the majority of the reported variables were not sensitive enough across technologies to consistently differentiate between concussed and non-concussed individuals. Understanding variable sensitivity was made more difficult given the absence of any reporting of reliability of the protocols and variables in the respective studies. CONCLUSION: Given the current status of the literature and the methodologies reviewed, there would seem little consensus on which gait parameters are best to determine return to play readiness after concussion. There is potential in this area for such technologies and protocols to be utilised as a tool for identifying and monitoring concussion; however, improving understanding of the variability and validity of technologies and protocols underpins the suggested directions of future research. Inertial measurement units appear to be the most promising technology in this aspect and should guide the focus of future research. IMPACT: Results of this study may have an impact on what technology is chosen and may be utilised to assist with concussion diagnosis and return to play protocols.
Keywords: concussion; dual task; gait; locomotion; concussion; dual task; gait; locomotion; 42 Health Sciences; 4207 Sports Science and Exercise; Neurosciences; Bioengineering; Traumatic Head and Spine Injury; Physical Injury - Accidents and Adverse Effects; Brain Disorders; Clinical Research; Traumatic Brain Injury (TBI); Toxicology; Brain Concussion; Cognition; Gait; Humans; Reproducibility of Results; Walking; Humans; Brain Concussion; Reproducibility of Results; Walking; Gait; Cognition